The Effect of Sharia Marketing on the Performance of MSMEs in West Java - Ardio Sagita; Nur Rislah Muzain; Ferdhy Ramadan; Roy Budiharjo (LPPM Universitas Negeri Jakarta, 2025)
This study examines the impact of Islamic marketing on Micro, Small, and Medium Enterprises (MSMEs) in West Java, Indonesia. Responses from 115 business owners across various sectors of West Java MSMEs were analyzed using SPSS and Smart Partial-Least Square (PLS). The findings indicate that Islamic marketing, encompassing four dimensions (Rabbaniyah, Akhlaqiyah, Al Waqiiyah, and Insaniyyah), significantly influences performance, with Islamic principles positively affecting the progress of MSMEs in the West Java region. Despite the limited sample size, the study's results encourage further research into market variations. This can benefit the success of MSMEs in West Java, Indonesia, for both practitioners and academics, by highlighting the importance of Islamic marketing networks. Additionally, the findings suggest that fostering a strong Islamic culture can promote positive behavior between businesses and customers. These insights are valuable for policymakers and business advisors aiming to tailor government support strategies for MSMEs in West Java and other Indonesian provinces, and could serve as a focus for future research. Future studies could explore these dynamics in other sectors and regions to develop a more comprehensive understanding of how Islamic marketing impacts business performance globally.